2008
DOI: 10.1016/j.cvfa.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity and Risk Management for Dairy Replacements

Abstract: Biosecurity, biocontainment, and disease risk management on dairy replacement operations are time- and labor-intensive, planned programs. Oftentimes the value of these programs is realized only after disease is introduced to a facility or a disease outbreak occurs. There is no "one-plan-fits-all;" each plan must be tailored to meet the needs of management's goals and expectations and problems specific to a production enterprise or geographic region. A standard framework applicable to biosecurity programs inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 126 publications
0
61
0
Order By: Relevance
“…cows and heifers) may be an important mode of Salmonella transmission. A study on biosecurity and risk management practices on dairy replacement rearing units in the United States by Maunsell and Donovan (2008) identified the minimisation of direct and indirect contact between different age groups of cattle as a practice to prevent new infections occurring in young stock. Grazing of heifers on cows pasture in such livestock systems should therefore be avoided to prevent new infections occurring in young stock.…”
Section: Discussionmentioning
confidence: 99%
“…cows and heifers) may be an important mode of Salmonella transmission. A study on biosecurity and risk management practices on dairy replacement rearing units in the United States by Maunsell and Donovan (2008) identified the minimisation of direct and indirect contact between different age groups of cattle as a practice to prevent new infections occurring in young stock. Grazing of heifers on cows pasture in such livestock systems should therefore be avoided to prevent new infections occurring in young stock.…”
Section: Discussionmentioning
confidence: 99%
“…Veterinarians play a major role as key informants on the BS for cattle holders; indeed, they consider their veterinary practitioner as the main source of information and adopt BSM based on veterinary advices (Gunn, Heffernan, Hall, McLeod, & Hovi, ; Heffernan, Nielsen, Thomson, & Gunn, ; Sayers et al., ). On the other hand, veterinarians also represent an important risk factor in terms of disease spread, as many studies have listed visitors, and more specifically professional visitors such as veterinarians, as a key risk factor in terms of bio‐exclusion (Anderson, ; Brennan & Christley, ; Canadian Food Inspection Agency, ; Maunsell & Donovan, ; Mee, Geraghty, O'Neill, & More, ; NADIS, ; Nöremark, Frössling, & Lewerin, ; Sayers et al., ; van Schaik et al., ; van Winsen et al., ). Meanwhile, an ongoing survey implemented in Belgian cattle farms (unpublished data) confirmed that most cattle holders were not feeling comfortable in asking their veterinarians to wear clean and/or specific work clothes or boots when visiting their premises; they prefer relying on their professionalism in that regard.…”
Section: Introductionmentioning
confidence: 99%
“…Buying youngstock, whilst not risk free, is often the most biosecure but may not meet the needs of the buyer. A comprehensive review of applying this risk assessment process to the sourcing of new dairy animals is given by Maunsell and Donovan (2008).…”
Section: Preventative Measuresmentioning
confidence: 99%